Paracoccidioides lutzii sp nov.: biological and clinical implications - Teixeira, Marcus de Melo; Theodoro, Raquel Cordeiro [UNESP]; Mendes de Oliveira, Fabiana Freire; Machado, Gabriel Capella [UNESP]; Hahn, Rosane Christine; Bagagli, Eduardo [UNESP]; San-Blas, Gioconda; Soares Felipe, Maria Sueli (Informa Healthcare, 2014)
Paracoccidioides lutzii, formerly known as 'Pb01-like' strains in the P. brasiliensis complex, is proposed as a new species based on phylogenetic and comparative genomics data, recombination analysis, and morphological characteristics. Conidia of P. lutzii are elongated, different from those of P. brasiliensis. P. lutzii occurs in the central and northern regions of Brazil. Studies comparing P. brasiliensis and P. lutzii may have significant clinical consequences for the diagnosis and treatment of paracoccidioidomycosis.
Keywords: Paracoccidioides brasiliensis; Paracoccidioides lutzii; paracoccidioidomycosis; speciation